Centesimal composition and physical-chemistry analysis of the edible mushroom Lentinus strigosus occurring in the Brazilian Amazon - Sales-campos, Ceci; Araujo, Lidia M.; Minhoni, Marli T.a.; Andrade, Meire C.n. (Academia Brasileira de Ciências, 2013)
Avaliou-se a composição centesimal e análise físico-química do Lentinus strigosus, um cogumelo comestível de ocorrência na Amazônia brasileira, produzidos em substratos alternativos à base de resíduos madeireiros e agroindustriais. Com este objetivo, determinou-se C, N, pH, sólidos solúveis, atividade de água, proteína, lipídios, fibra total, cinzas, carboidratos e energia. Os substratos foram formulados a partir de serragem de Simarouba amara Aubl. (marupá), Ochroma piramidale Cav. ex. Lam. (pau-de-balsa) e Anacardium giganteum (cajuí); e do estipe de Bactris gasipaes Kunth (pupunheira) e de Saccharum officinarum (cana-de-açúcar). Os resultados demonstraram que: a composição nutricional do L. strigosus variou com o substrato de cultivo; os valores de proteína encontrados nos cogumelos cultivados nos diferentes substratos (18 - 21,5%) variaram de acordo com o substrato, sendo considerados elevados; os sólidos solúveis presentes nos cogumelos podem ter relação com vitaminas hidrossolúveis do complexo B; o L. strigosus pode ser considerado um importante alimento devido suas características nutricionais: alto teor de proteína, carboidratos metabolizáveis e fibras; baixos teores de lipídios e de calorias.

The centesimal composition and the physical and chemical analyses of Lentinus strigosus, an edible mushroom occurring in the Brazilian Amazon and produced in alternative substrates based on wood and agroindustrial residues, were evaluated. For this purpose, the C, N, pH, soluble solids, water activity, protein, lipids, total fiber, ash, carbohydrate, and energy levels were determined. The substrates were formulated from Simarouba amara Aubl. (“marupá”), Ochroma piramidale Cav. Ex. Lam. (“pau-de-balsa”) and Anacardium giganteum (“cajuí”) sawdust and Bactris gasipaes Kunth (“pupunheira”) stipe and Saccharum officinarum (sugar cane bagasse). The results indicated that the nutritional composition of L. strigosus varied with the substrate of cultivation; the protein levels found in mushrooms grown in the different substrates (18 – 21.5%) varied with the substrate and was considered high; the soluble solids present in the mushrooms could have a relation with complex B hydrosoluble vitamins. L. strigosus could be considered as important food owing to its nutritional characteristics such as high protein content, metabolizable carbohydrates and fibers, and low lipids and calories content.
Keywords: cogumelos comestiveis; valor nutricional; minerais; proteinas; fibras; edible mushroom; nutritional value; minerals; protein; fibers